2017
DOI: 10.2174/1570159x14666160708231216
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Evidence for the Primacy of Mania Hypothesis

Abstract: Background: Athanasios Koukopoulos proposed the primacy of mania hypothesis (PoM) in a 2006 book chapter and later, in two peer-reviewed papers with Nassir Ghaemi and other collaborators. This hypothesis supports that in bipolar disorder, mania leads to depression, while depression does not lead to mania.Objective: To identify evidence in literature that supports or falsifies this hypothesis.Method: We searched the medical literature (PubMed, Embase, PsycINFO, and the Cochrane Library) for peer-reviewed papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 78 publications
(48 reference statements)
2
10
0
Order By: Relevance
“…Specifically, when directly compared, BD‐DP presented with smaller bilateral presubiculum/subiculum than BD‐MP. This could be in line with the opposite dysfunctions in reward processing that patients present during manic and depressive episodes: a state of hyper‐dopaminergia during hypomania/mania and a state of hypo‐dopaminergia during depression . These neurobiological patterns correspond respectively to an excessive involvement in pleasurable activities in mania and to anhedonia in depression.…”
Section: Discussionsupporting
confidence: 56%
“…Specifically, when directly compared, BD‐DP presented with smaller bilateral presubiculum/subiculum than BD‐MP. This could be in line with the opposite dysfunctions in reward processing that patients present during manic and depressive episodes: a state of hyper‐dopaminergia during hypomania/mania and a state of hypo‐dopaminergia during depression . These neurobiological patterns correspond respectively to an excessive involvement in pleasurable activities in mania and to anhedonia in depression.…”
Section: Discussionsupporting
confidence: 56%
“…The first was a FC study and showed reduced FC in risk gene carriers in the right hemisphere, between the amygdala and the anterior subgenual cingulate cortex during a face-matching task, then also during emotional processing of faces (Poletti et al, 2018). Consistently, abnormalities in FC in limbic-cingulate network have been previously found in BD and linked with predominant polarity of mood states (Kotzalidis et al, 2017;Janiri et al, 2017). The second was a DTI study of EAAT2-181A > C (SLC1A2 gene) rs4354668 on WM integrity and found that risk G allele carriers had lower axial diffusivity compared to T/T homozygotes when subjected to high-stress levels, but higher diffusivity than T/T when exposed to low stress.…”
Section: Discussionmentioning
confidence: 61%
“…Thinner cortical areas in youth with PBD, i.e., ACC, PCC, OFC, IPC, SMG, LC, are part of two interconnected networks involved in emotion regulation and impulse control. The rostral part of the ACC and the medial and lateral parts of the OFC belong to the affective network (AN) (68)(69)(70). The OFC and ACC are densely interconnected with the amygdala and the other subcortical limbic and paralimbic regions through specific feedback and feedforward pathways that serve to convey attention to motivationally relevant stimuli and provide information about the emotional salience or significance of external stimuli in order to rapidly perceive reward contingency (35).…”
Section: Discussionmentioning
confidence: 99%